Exploring tranquility: Eastern and Western perspectives - Christoffersen, Vincent Ringgaard; Škodlar, Borut; Henriksen, Mads Gram (Frontiers in Psychology, 2022)
Although tranquility is a fundamental aspect of human life, the experiential nature of tranquility remains elusive. Traditionally, many philosophical, religious, spiritual, or mystical traditions in East and West have strived to reach tranquil experiences and produced texts serving as manuals to reach them. Yet, no attempt has been made to compare experiences of tranquility and explore what they may have in common. The purpose of this theoretical study is to explore the experiential nature of tranquility. First, we present examples of what we consider some of the most central experiences of tranquility in Eastern and Western traditions. For the sake of simplicity, we sort these examples into four categories based on their experiential focus: the body, emotions, the mind, and mysticism. Second, we offer an exploratory account of tranquility, arguing that the different examples of tranquility seem to share certain experiential features. More specifically, we propose that the shared features pertain both to the content or quality of the tranquil experiences, which involves a sense of presence and inner peace, and to the structure of these experiences, which seems to involve some degree of detachment and absorption.